The Role of Energy Storage in Unlocking the Full Potential of Renewable Resources - Murad Salem Mohamed Alrawiq; Osama Hamad Abd Alsalam Alasamar Alhadheeri; Ahmed Salem Mohamed Alrwig (African Journal of Advanced Pure and Applied Sciences, 2024)
Energy storage technologies are essential for maximizing the potential of renewable energy sources by addressing their inherent intermittency and enhancing grid stability. This research paper explores various energy storage technologies, including lithium-ion batteries, lead-acid batteries, sodium-sulfur batteries, flow batteries, pumped hydro storage, thermal energy storage, compressed air energy storage, and flywheel energy storage. It examines their applications, advantages, and disadvantages, alongside real-world case studies demonstrating their impact on grid stability and renewable integration. Despite significant advancements, the widespread adoption of energy storage faces challenges such as high costs, resource constraints, technological limitations, regulatory hurdles, and environmental concerns. However, the future outlook remains promising due to ongoing technological innovations, supportive policies, and evolving market dynamics. The paper highlights the need for sustainable supply chains, decentralized storage solutions, and modernized grid infrastructure to fully leverage the potential of energy storage technologies. These developments are crucial for achieving a sustainable, resilient, and reliable energy future.